Pengaruh Citra Dan Kualitas Pelayanan Terhadap Loyalitas Pasien Dimediasi Kepuasan Pasien Pada Rumah Sakit Provita - Sabet, Eli; Rasyid, Abdul; Pongtiku, Arry; Sonjaya, Yaya; Marihi, La Ode (Journal of Economics Review (JOER), 2023)
This study aims to determine the effect of image and service quality on patient loyalty mediated by patient satisfaction at Provita Hospital. The population in this study were all patients, both general, BPJS and insurance who had received treatment or treatment in 2023 at Provita Jayapura Hospital. The sample in this study is 90 patients. The analytical method used is mediation analysis with data processing tools using SmartPls version 3.00 software. Based on the tests conducted, it shows that image, service quality and patient satisfaction directly affect patient loyalty at Provita Jayapura Hospital. Image does not directly affect patient satisfaction at the Provita Jayapura hospital. Service quality directly affects patient satisfaction at the Provita Jayapura hospital. Patient satisfaction can mediate the relationship between service quality and patient loyalty at the Provita Jayapura hospital. Patient satisfaction cannot mediate the relationship between image and patient loyalty at the Provita Jayapura hospital